PRO-ACTIVE LEGISLATIVE TARGETS 1990 (900000). PRO-ACTIVE PROPOSAL. MASSACHUSETTS HIRING DISCRIMINATION. (Tufts Archival Research Center, 2007)
Four separate pro-active legislative proposals from the state of Massachusetts addressing issues of hiring discrimination, indoor air quality, tobacco sampling preemption, and local restaurant restriction rollbacks. Identifies resources needed to gain proponents of each bill as: economic analysis, legal memorandum, expert witnesses, coalition allies, Tobacco Institute grassroots mobilization, company resources, and media resources.